2016
DOI: 10.1007/s12088-016-0627-z
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial, Anticancer and Neuroprotective Activities of Rare Actinobacteria from Mangrove Forest Soils

Abstract: Mangrove is a complex ecosystem that contains diverse microbial communities, including rare actinobacteria with great potential to produce bioactive compounds. To date, bioactive compounds extracted from mangrove rare actinobacteria have demonstrated diverse biological activities. The discovery of three novel rare actinobacteria by polyphasic approach, namely MUSC 115, MUSC 117 and MUSC 78 from mangrove soils at Tanjung Lumpur, Peninsular Malaysia have led to the screening on antibacterial, anticancer and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 65 publications
(87 reference statements)
0
59
0
Order By: Relevance
“…As a result, there is an increasing push to search for bioactive compounds from natural sources to serve as alternative antimicrobials (Tan et al, 2015b, 2016a; Azman et al, 2016; Chan et al, 2016) Reports on the occurrence of antimicrobials in F. velutipes mushroom are also well documented. The antimicrobial activities of extracts from different parts of F. velutipes have been the focus of several studies.…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…As a result, there is an increasing push to search for bioactive compounds from natural sources to serve as alternative antimicrobials (Tan et al, 2015b, 2016a; Azman et al, 2016; Chan et al, 2016) Reports on the occurrence of antimicrobials in F. velutipes mushroom are also well documented. The antimicrobial activities of extracts from different parts of F. velutipes have been the focus of several studies.…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…Phenolic compounds constitute hydroxyl functional groups attached to aromatic compounds [108] . The lower bond dissociation energy (BDE) between hydroxyl functional group, renders hydrogen a good leaving group, and, the parent compound -phenolic compounds -overall, as good scavengers of ROS [109,110] .…”
Section: Discussionmentioning
confidence: 99%
“…and her colleagues investigated biological activities of Microbacterium mangrovi MUSC 115 T , Sinomonas humi MUSC 117 T and Monashia flava MUSC 78 T isolated from the mangrove forest of Malaysia. From their study, it was shown that methanolic extracts from 3 bacterial species contained a number of pyrrolopyrazines and either one of these extracts were effective against batteries of pathogenic bacteria, cancer cell lines and neuroprotection models [108] . Given that past studies have highlighted the presence of compound (6) in microbial extract with antioxidant potentials [40,48,100] , further points to its likely role in inducing antioxidant effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that marine Actinobacteria exhibit distinct characteristics from those terrestrial counterparts and therefore produce more potentially novel bioactive compounds [190,192] . Thus, marine environment is a potential source for isolation of novel Actinobacteria in which increasing evidences on the discovery of novel antibiotic and industrially important enzyme from marine Actinobacteria [193][194][195][196] . Likewise, 80% of the reviewed studies demonstrated the isolation of Streptomyces with anti-Vibrio activity from aquatic environments such as marine sediments, marine invertebrates and mangrove ecosystems.…”
Section: Aquatic Environmentsmentioning
confidence: 99%